Recenzja książki pt.„Małżeństwo i rodzina w świadomości młodzieży maturalnej – stabilność i zmiana”Janusza Mariańskiego - Mianowana, Mianowana (Nursing in the 21st Century, 2013)
RECENZJA KSIĄŻKI PT.„MAŁŻEŃSTWO I RODZINA W ŚWIADOMOŚCI MŁODZIEŻY MATURALNEJ – STABILNOŚĆ I ZMIANA”JANUSZA MARIAŃSKIEGONowadays, as a community, we experience the social modernization; we live in times of doctrinal, moral and social dilemmas. This is why we ask a question for moral condition of society, especially this younger part of it. In such conditions, we see not only fears and threats but also chances and hopes for future. The book “Marriage and family in consciousness of high school youth – stability and changes.” by Janusz Mariański shows us the level of consciousness of high school youth, concerning conjugal and family life, it means pro-family ideology, respectable pro-family values and norms. The book consists of six chapters and is very interesting publishing item, in which every reader can find some facts that could become inspiration for reflection.